Competition is not necessarily a barrier to community mobilisation among sex workers: an intervention planning assessment from Zimbabwe - Mtetwa, Sibongile (BMC Public Health, 2015)
BACKGROUND: Community mobilization among female sex workers (SWs) is recognized as an effective strategy to empower SWs and increase their uptake of health services. Activities focus on increasing social cohesion between SWs by building trust, strengthening networks, and encouraging shared efforts for mutual gain. Several studies, however, suggest that high levels of interpersonal competition between SWs can pose a barrier to collective action and support. We conducted a study to examine levels of perceived competition between SWs in Mutare, Hwange and Victoria Falls in Zimbabwe in order to inform development of a community-based intervention for HIV prevention and treatment. This paper focuses on our qualitative findings and their implications for the design of HIV programming in the Zimbabwean context. METHODS: Following a respondent driven sampling (RDS) survey, we explored issues related to social cohesion amongst SWs in Mutare, Hwange and Victoria Falls through in-depth interviews conducted with 22 SWs. Interviews examined dynamics of SWs’ relationships and extent of social support, and were analyzed using thematic content analysis using the constant comparative method. Findings are contextualised against descriptive data extracted from the survey, which was analysed using Stata 12, adjusting for RDS. RESULTS: Across all sites, women described protecting each other at night, advising each other about violent or non-paying clients, and paying fines for each other following arrest. In Mutare, women gave additional examples, including physically attacking problem clients, treatment adherence support and shared saving schemes. However, interviews also highlighted fierce competition between women and deep mistrust. This reflects the reported mix of competition and support from the survey of 836 women (Mutare n = 370, Hwange n = 237, Victoria Falls n = 229). In Mutare, 92.8 % of SWs agreed there was a lot of competition; 87.9 % reported that SWs support each other. This contrasted with Victoria Falls and Hwange where fewer agreed there was competition between SWs (70.5 % and 78.0 %), but also fewer reported that SWs support each other at work (55.2 % and 51.2 %). CONCLUSIONS: Women reported being most likely to support each other when confronted with serious danger but maintained high levels of competition for clients, suggesting competition at work does not represent a barrier to support. Examples of practical assistance between SWs provide entry points for our planned community mobilization activities, which aim to broaden trust and support among SWs while acknowledging their professional competition.